Objective Improvement in Cognitive Function following Aortic Coarctation Repair in an Adult - Hayes, Danielle; French, Bryce; Tan, Swee Lian (AORTA, 2021)
Coarctation of the aorta is a rare finding in adults and can present with vague symptoms. We report a case of a 64-year-old cognitively impaired female who presented with fatigue and tinnitus. After extensive workup, she was diagnosed with coarctation of the aorta and subsequently underwent repair. After operative intervention for her coarctation, her cognitive impairment was found to have an objective improvement evidenced by the Montreal Cognitive Assessment.
Keywords: aortic coarctation; cognitive impairment; Montreal cognitive assessment